Analysis of strategic studies positioning leading European universities in the international information space - Shcherbak, I. (Problems of Engineer-Pedagogical Education, 2021)
The essence of «information space», «international information space», «strategy of positioning a leading university in the international information space» is discussed the article. Having defined these concepts, it can be argued that positioning performs one of the main functions of the classical and modern control theory. The author analyzes the scientific works of classical and modern representatives of various management schools on strategic research on the positioning of the leading universities of Europe in the international information space, namely: the school of scientific management, the administrative school of management, a quantitative school, the school of conceptual management for goals, the school of social systems. The analysis made it possible to conclude that the work of management schools depends on the use of external information and depends on changes in the environment and, using a synergistic approach, we can formulate factors that affect the work of educational institutions and stimulate leading universities to change towards the development of the environment. The author took into account the current development conditions of the education in Ukraine, the urgent issue is the management of an educational institution that seeks to become more popular and competitive, the researcher reviewed the work of scientists related to the problems of positioning strategies of leading universities. This made it possible to find out that a significant influence on the formation of the strategic goals of enterprises and educational institutions led to a transition from an industrial economy to an information one. The scientist believes that in order to achieve a certain position, a university must have a stable positioning strategy. According to the author, this is the process of developing the positioning of a university, which has planning and management decisions and meets the needs of consumers. There should also be a plan to create your own brand in order to have special characteristics that differ from the products of other higher education institutions.